Community empowerment in improving health status - Nur Syamsi Norma Lalla (Edukasi Ilmiah Indonesia, 2024)
Community empowerment is an important approach to improving health at various social, economic, and cultural levels. This approach emphasizes the active role of communities in managing and improving their own well-being, including aspects of physical, mental, and social health. Community empowerment involves the process of developing the knowledge, skills, and capacity of individuals and groups to understand and overcome health problems. This can include health education, the promotion of healthy lifestyles, strengthening access to health services, and building community-friendly health infrastructure. Through collaboration between governments, non-governmental organizations, and the private sector, community empowerment can be an effective means to improve the accessibility and quality of health services, as well as to reduce health disparities among different groups of people. The implementation of community empowerment programs has shown a significant impact on increasing health knowledge, improving healthy living behaviors, and reducing preventable disease and mortality. The development of strategies and policies that support community empowerment is an important step in achieving sustainable development goals in the health sector